Arabic Language and Religious Identity: Challenges of Globalization in the Modern Era - `Ainina, Mutanafisah Qurrotu; Islam, Saiful; Nanang Qosim, Muhammad (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
In the midst of the dominance of global languages like English and the shift from fus-ha to 'amiyah, the Arabic language faces existential challenges. This study emphasizes the importance of preservation strategies through curriculum and digital technology. Arabic, as the language of the Qur'an, holds a central position in shaping the religious identity of Muslims worldwide. However, the era of globalization presents significant challenges to its sustainability, particularly due to the global dominance of English in the realms of science, technology, and media, as well as the increasing shift from standard Arabic (fus-ha) to local dialects (‘amiyah). This study explores these challenges through a qualitative literature review, integrating linguistic, sociocultural, and technological perspectives. The findings reveal that while Arabic remains a core symbol of Islamic religious identity, it faces pressures from linguistic hybridization, educational transitions, and technological marginalization. Nonetheless, globalization also presents opportunities through the proliferation of Arabic-based digital media, online education, and language learning applications. Strategic efforts to preserve Arabic include curriculum strengthening, technological integration, and global cultural promotion. This study underscores the enduring relevance of Arabic not only as a medium of religious expression but also as a vehicle for sustaining Islamic values and cultural heritage in a rapidly evolving global context.